Business cycle synchronisation in the euro area: the case of small countries - Correia, Leonida (2008)
Business cycle synchronisation is a necessary condition for the successful implementation of a common monetary policy, according to the theory of Optimum Currency Area. This paper focuses on the European Monetary Union (EMU) providing a descriptive analysis of the association between the aggregate Euro area and nine member states’ business cycles in 1980:1–2004:4. Overall, we find that, since the inception of EMU, business cycles of the larger member-states have been increasingly synchronised with the aggregate Euro area cycle, with the only exception of Spain, while results are rather mixed in the case of smaller countries. We further document that since 1997 business cycle synchronisation has become weaker in a number of countries, such as Belgium, the Netherlands and Greece.